The correlation between age of first dating and sexual behavior of adolescents and young adults in indonesia - Devi Elfita Sari; Dewi Rokhanawati (Journal of Health Technology Assessment in Midwifery, 2018)
Premarital sexual behavior among Indonesian adolescents currently becomes easier to be found than previous generation. Based on health survey in 2017, both female and male adolescents admitted that they experienced dating since the aged of 16. Data showed that adolescents who were in relationship admitted having premarital sex than the common adolescents. This study’s objectives was to investigate the correlation between age of first dating and sexual behavior among adolescents and adults in Indonesia. The sample of this study involved respondents of health demographic survey in Indonesia 2012 who fulfilled the inclusion criteria of men and women aged 15-24 years and unmarried. This research was a quantitative research using descriptive analytic research design with cross sectional approach. The age of first dating on adolescents was higher (96.2%) than young adults (3.8%). The numbers of dating teenagers and adults with sexual behavior (90.3%) was higher than those without sexual behavior (9.7%). Chi-Square correlation test results by using 95% of confidence revealed p-value equal to 0.004 0.05 with value of correlation coefficient equal to 0.023 indicating positive and significant correlation. Conclusion: There was correlation between age of first dating and sexual behavior on adolescents and adults in Indonesia.